Pandangan Mufassir Terhadap Ya’juj dan Ma’juj dalam QS. Al-Anbiya: 96 - Muhammad Zaki; Achyar Zein (Jurnal Penelitian Ilmu Ushuluddin, 2026)
This study aims to analyze the interpretations of Qur’anic exegetes (mufassir) regarding Surah Al-Anbiya verse 96, which discusses Gog and Magog (Ya’juj and Ma’juj) as one of the major signs of the Day of Judgment. The focus of this research includes the exegetical understanding of their nature, the process of their emergence, and the impact they bring. This study employs a qualitative approach through library research by examining classical and contemporary tafsir literature. The findings reveal that exegetes generally agree that Gog and Magog are entities that will appear before the Day of Judgment in enormous numbers and will cause widespread disruption to human life. However, differences arise in interpreting their nature. Classical exegetes tend to view them as real human beings who will physically emerge, while contemporary scholars allow for a symbolic interpretation, considering them as representations of destructive forces. Furthermore, their emergence is described as sudden, massive, and uncontrollable, leading to significant destruction on earth. In conclusion, this study demonstrates that the interpretation of Surah Al-Anbiya verse 96 is dynamic and influenced by the methodological approaches of the exegetes. Despite differing perspectives, there is a shared understanding that the emergence of Gog and Magog represents a major event with profound implications for humanity.